CsgA production by Escherichia coli O157:H7 alters attachment to abiotic surfaces in some growth environments - Goulter-Thorsen, R.; Taran, E.; Gentle, I.; Gobius, K.; Dykes, Gary (2011)
The role of curli expression in attachment of Escherichia coli O157:H7 to glass, Teflon, and stainless steel (SS) was investigated through the creation of csgA knockout mutants in two isolates of E. coli O157:H7. Attachment assays using epifluorescence microscopy and measurements of the force of adhesion of bacterial cells to the substrates using atomic force microscopy (AFM) force mapping were used to determine differences in attachment between wild-type (wt) and csgA-negative (ΔcsgA) strains following growth in four different media. The hydrophobicity of the cells was determined using contact angle measurements (CAM) and bacterial adhesion to hydrocarbons (BATH). The attachment assay results indicated that ΔcsgA strains attached to glass, Teflon, and SS surfaces in significantly different numbers than their wt counterparts in a growth medium-dependent fashion (P < 0.05). However, no clear correlation was seen between attachment numbers, surface type, or growth medium. No correlation was seen between BATH and CAM results (R2 < 0.70). Hydrophobicity differed between the wt and ΔcsgA in some cases in a growth medium- and method-dependent fashion (P < 0.05). AFM force mapping revealed no significant difference in the forces of adhesion to glass and SS surfaces between wt and ΔcsgA strains (P > 0.05) but a significantly greater force of adhesion to Teflon for one of the two wt strains than for its ΔcsgA counterpart (P < 0.05). This study shows that CsgA production by E. coli O157:H7 may alter attachment behavior in some environments; however, further investigation is required in order to determine the exact relationship between CsgA production and attachment to abiotic surfaces.